The first results of an international clinical trial VICTORY:the efficacy and safety of antihypertensive valsartan monotherapy and the fixed combination of valsartan and hydrochlorothiazide usingdifferent dosage regimens in patients with 1-2 degree arterial hypertension - E Evgen'evna Chazova; T V Martyniuk (Системные гипертензии, 2015)
On behalf of the group of russian researchers. The aim of the VICTORY study was to estimate the efficacy and safety of valsartan monotherapy using different dose regimes (Valsacor® 80, 160, 320 mg) and its fixed combination with hydrochlorothiazide (HCTZ) using different dosage regimens [Valsacor® H160 (valsartan 160 mg + HCTZ12.5 mg), Valsacor® H320 (valsartan 320 mg + HCTZ 12.5 mg) Valsacor® HD320 (valsartan 320 mg + HCTZ 25 mg)] in reaching the target level of blood pressure (BP) in patients with 1-2 degree arterial hypertension (AH).Materials and methods. There are 130 patients with 1-2 degree AH were enrolled in the open international multicenter prospective randomized study from 7 cities in 8 Russian Clinical Centers in Russia. The starting dose of valsartan depended upon the previous antihypertensive treatment: for previously untreated patients - 80 mg (Valsacor® 80 mg, KRKA, Slovenia) with randomization into 4 parallel groups (n=108) for the patients receiving antihypertensive therapy during the screening, after washout 7-day period of Valsacor® 160 mg application with randomization into 8 parallel groups (n=22). Besides the dynamics of clinical BP, we evaluated the impact of therapy on pulse ware velocity, erectile function (in men) and the quality of life. Results. The clinical BP in 130 patients with AH with age of 55.6±11.5 years (65% women) at the moment of inclusion into the study was 157.6/95.1 mm Hg. The BP was reduced to 140.9/85.3 mm Hg on the 4-week of valsartan 80 or 160 mg application. Valsartan titration or the combination of valsartan and HCTZ on the 8-week helped to reduce BP to 135.2/83.5 mm Hg. The 16-week treatment showed the BP reduced to 129.2/79.4 mm Hg. ( p